Implementasi Kebijakan Perhutanan Sosial di Lembaga Pengelola Hutan Nagari (LPHN) Nagari Sungai Rimbang, Kab. Lima Puluh Kota - Maulani Azizah; Sinta Westika Putri (Lembaga Yasin AlSys, 2026)
Although studies on Social Forestry have been widely conducted, research that specifically discusses policy implementation in the Nagari Forest Management Institution (LPHN) of Nagari Sungai Rimbang remains limited. This study aims to analyze the implementation of Social Forestry policy and identify the driving and inhibiting factors in its implementation at the local level. This study used a qualitative approach with a descriptive case study design. Research informants were selected through purposive sampling, including UPTD KPHL Lima Puluh Kota, the nagari government, LPHN administrators, forest managers, forest farmer groups, and the community. Data were collected through observation, in-depth interviews, and documentation, and were then analyzed using the Miles and Huberman model through the stages of data reduction, data display, and conclusion drawing. The results showed that the implementation of Social Forestry policy had been carried out administratively through the existence of LPHN, the division of roles among actors, and policy communication. However, its implementation has not been optimal because communication has not been evenly distributed, community participation remains low, resource capacity is limited, technical assistance is minimal, and there are constraints related to regional accessibility. These findings enrich the study of public policy implementation based on local institutions and emphasize the importance of strengthening communication, LPHN capacity, and community participation in sustainable nagari forest management. The implications of this study provide practical references for local governments, forest management institutions, and communities in strengthening Social Forestry governance based on local participation.